Sex-specific differences in fetal and infant growth patterns: a prospective population-based cohort study. Issue 1 (December 2016) - Broere-Brown, Zoe; Baan, Esme; Schalekamp-Timmermans, Sarah; Verburg, Bero; Jaddoe, Vincent; Steegers, Eric
Abstract Background The objective of this study was to assess whether sex-specific differences in fetal and infant growth exist. Methods This study was embedded in the Generation R Study, a population-based prospective birth cohort. In total, 8556 live singleton births were included. Fetal growth was assessed by ultrasound. During the first trimester, crown-rump-length (CRL) was measured. In the second and third trimester of pregnancy head circumference (HC), abdominal circumference (AC) and femur length (FL) were assessed. Information on infant growth during the first 2 years of life was obtained from Community Health Centers and included HC, body weight and length. Results In the first trimester, male CRL was larger than female CRL (0.12 SD [95% CI 0.03, 0.22]). From the second trimester onwards, HC and AC were larger in males than in females (0.30 SD [95% CI 0.26, 0.34] and 0.09 SD [95% CI 0.05, 0.014], respectively). However, FL in males was smaller compared to female fetuses (0.21 SD [95% CI 0.17, 0.26]). Repeated measurement analyses showed a different prenatal as well as postnatal HC growth pattern between males and females. A different pattern in body weight was observed with a higher body weight in males until the age of 12 months where after females have a higher body weight. Conclusions Sex affects both fetal as well as infant growth. Besides body size, also body proportions differ between males and females with different growth patterns. This sexual dimorphism might arise from differences in fetal programming with sex specific health differences as a consequence in later life.